The substantiation of mathematics abilities test contents’ structure of the primary school pupils - Kiseliovas, Arkadijus; Kiseliova, Danutė (Lietuvos matematikos rinkinys, 2001)
We have performed a statistic analysis of mathematics textbooks and of general education of the fourth – formers according to the teaching contents’ categories and their operationality. We have divided into three categories the standard requirements for the pupil’s communicative abilities, mathematics abilities and skills, the abilities linked with the expression of mathematics thinking in soling problems. The classification of the pupil’s cognitive activity was done of Cole’s taxonomy of cognitive activity skills reflecting three categories linked with the results of learning in the cognitive sphere: knowledge, skills and teaching.